Guidelines for South African boatbuilding companies to market boats in China - Ding, Yi (Cape Peninsula University of Technology, 2008)
The opening ceremony of the 29th Olympic Games displayed a historical tapestry of Chinese culture to the world. At the same time, the 2008 Games presented new opportunities for Chinese people to experience aspects of the outside world, which may have previously been closed to them. Aquatic sport is one such example, especially recreational sailing and yachting, which are novel concepts within Chinese society. Given China’s rapid economic growth, this burgeoning market has potential for South African exporters, including the recreational marine sector. However, South African manufacturers have not promoted their products, many of which are of a high standard, in this market. Are there barriers, which may prevent successful exports of marine products to China? Would a deeper understanding of China’s unique business culture assist the local boatbuilding industry to successfully present their products in China? The purpose of this study is to assist South African boat builders to expand their business operations in China by developing guidelines for marketing strategy formulation. The entire research study shows that there are indeed opportunities to market boats in China, while the market is mainly located in coastal cities. The research reviewed South African trade with China, successful entry of South African companies into the Chinese market, and shows that potential does exist for penetration of the Chinese market by South African marine industries. Based on a further review of the internal marketing environment in China, it is established that a unique feature of Chinese business culture, termed Guanxi, might be a major barrier for penetration of the Chinese boat market by the South African marine industry.
Thesis (MTech (Marketing))--Cape Peninsula University of Technology, 2008
Keywords: Guidelines for marketing strategy formulation; Market boats in China; South African boat building; South African exporters; Guanxi networking